2012
DOI: 10.1515/cclm-2011-0823
|View full text |Cite
|
Sign up to set email alerts
|

Increased concentrations of growth factors and activation of the EGFR system in breast cancer

Abstract: Our study demonstrated a profound activation of the EGFR system. HB-EGF was increased by factor 10 in cancer tissue and related to the biological aggressiveness of the tumors, and pHER2, HB-EGF and BTC were associated with poor clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…4-6). Because the expression of high-affinity ligands such as HB-EGF and TGFa has been implicated in various cancers (15)(16)(17)(18) and in the lack of response or acquired resistance to cetuximab (13,14), our results indicate that GC1118 may have a broad cancer patient pool including those patients progressed after treatment with current EGFR-targeted therapeutics. On the basis of these promising preclinical results, a phase I clinical trial is under study (ClinicalTrials.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…4-6). Because the expression of high-affinity ligands such as HB-EGF and TGFa has been implicated in various cancers (15)(16)(17)(18) and in the lack of response or acquired resistance to cetuximab (13,14), our results indicate that GC1118 may have a broad cancer patient pool including those patients progressed after treatment with current EGFR-targeted therapeutics. On the basis of these promising preclinical results, a phase I clinical trial is under study (ClinicalTrials.…”
Section: Discussionmentioning
confidence: 87%
“…An increased expression of high-affinity ligands, such as TGFa and HB-EGF, was also observed in a mouse colorectal cancer model with acquired resistance to cetuximab (14). An elevated level of TGFa or HB-EGF has been observed in other cancers, including advanced ovarian cancer, breast cancer (15)(16)(17), and lung cancer (18), and is associated with worse clinical survival.…”
Section: Introductionmentioning
confidence: 91%
“…Synergy between NTS and EGF was previously described on DNA synthesis in primary adult rats' hepatocytes [28], and the regulation between these two factors appears to be independent of oncogenic characteristics of the cells. EGF was detected in normal and tumoral breast tissues, with a higher expression found in normal tissues adjacent to tumor [29]. We previously showed that NTS is expressed in normal breast epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…EGF “like” ligands are largely implicated in breast cancer progression, yet, most reports have only studied the expression of ligands specific to EGFR, or those specific to HER3. For example, in one case a 10 fold increase of HB-EGF in cancer tissues was reported, and in another a high proportion of the four neuregulins and major isoforms were expressed in the cytoplasm of DCIS and IDC of the breast [29,43,44]. In both cases, deleterious effects of growth factors are often in HER2 overexpressing cells, indicating that EGFR/HER2 and/or HER3/HER2 dimers are related to biological aggressiveness [29].…”
Section: Discussionmentioning
confidence: 99%
“…The patients underwent surgery according to Danish Breast Cancer Guidelines (www.DBCG.dk) and all patients provided written consent. The HER2 protein concentration in the cancer tissue was measured quantitatively and published in Olsen et al [14]. Ninety-three patients were selected for this present study based on the degree of HER2 in the cancer tissue.…”
Section: Patients and Materialsmentioning
confidence: 99%